2014
DOI: 10.1210/jc.2013-3272
|View full text |Cite
|
Sign up to set email alerts
|

In Older Men an Optimal Plasma Testosterone Is Associated With Reduced All-Cause Mortality and Higher Dihydrotestosterone With Reduced Ischemic Heart Disease Mortality, While Estradiol Levels Do Not Predict Mortality

Abstract: Optimal androgen levels are a biomarker for survival because older men with midrange levels of T and DHT had the lowest death rates from any cause, whereas those with higher DHT had lower IHD mortality. Further investigations of the biological basis for these associations including randomized trials of T supplementation are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
126
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 44 publications
10
126
1
4
Order By: Relevance
“…This may reflect tissue actions of DHT, with experimental studies demonstrating attenuation of development of atherosclerosis with DHT exposure [38]. We have previously reported that higher DHT is associated with reduced mortality from ischaemic heart disease in older men [39], thus our current findings in younger men may be important for the consideration of future interventional studies. Of note, our results reinforce the importance of T, DHT and E2 rather than SHBG or LH, for risk stratification, particularly when LC-MS is available for the assay of these sex steroids.…”
Section: Discussionmentioning
confidence: 58%
“…This may reflect tissue actions of DHT, with experimental studies demonstrating attenuation of development of atherosclerosis with DHT exposure [38]. We have previously reported that higher DHT is associated with reduced mortality from ischaemic heart disease in older men [39], thus our current findings in younger men may be important for the consideration of future interventional studies. Of note, our results reinforce the importance of T, DHT and E2 rather than SHBG or LH, for risk stratification, particularly when LC-MS is available for the assay of these sex steroids.…”
Section: Discussionmentioning
confidence: 58%
“…The similarity of this index of androgen status with the temporal profile of testosterone and of DHT is consistent with the relative stability of the DHT/testosterone ratio (median 0.10) across a large population of men. Nevertheless, although DHT is usually converted from testosterone by 5a reductase, the independent backdoor pathway that synthesizes DHT bypassing testosterone (54) allows for independent regulation of serum DHT levels with potentially differential effects on health outcomes such as cardiovascular disease and mortality (55,56). Hence, this novel response metameter, incorporating simultaneous measurements of both testosterone and DHT, may provide a more comprehensive metric to characterize androgen status for individual men and male populations where the impact on the two major androgens may diverge.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that normal testosterone levels may offer protection against the development of atherosclerosis in middle-aged men. Optimal androgen levels seem to be a biomarker for survival because men with mid-range levels of testosterone and dihydro-testosterone were recently reported to have the lowest death rate from any cause (18). This was obvious also in the present study, where intermediate testosterone concentrations (9.26-14.90 nmol/l) considered as 'lownormal' were protective against CVD death in the followup of the patients, and the men with suppressed testosterone in the acute phase had increased risk of subsequent ACS in the follow-up of 6 years.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%